Novel Missense Variant in Heterozygous State in the BRPF1 Gene Leading to Intellectual Developmental Disorder With Dysmorphic Facies and Ptosis - Naseer, Muhammad Imran; Abdulkareem, Angham Abdulrahman; Guzmán-Vega, Francisco J.; Arold, Stefan T.; Pushparaj, Peter Natesan; Chaudhary, Adeel G.; AlQahtani, Mohammad H. (Frontiers in Genetics, 2020)
The BRPF1 gene (Bromodomain and PHD Finger Containing 1) encodes a bromodomain, PHD finger and chromo/Tudor-related Pro-Trp-Trp-Pro (PWWP) domain containing protein. Mutations in BRPF1 gene is leading to intellectual developmental disorder with dysmorphic facies, ptosis (IDDDFP) along with microcephaly. In this report the Whole exome sequencing (WES) was performed for the affected members of the family to study the novel mutations. WES data analysis was confirmed by subsequent Sanger sequencing validation. We report a novel missense variant in heterozygous state in the exon 3 of BRPF1 gene (ENST383829: c.1054G>C and p.Val352Leu). The mutation was ruled out in 100 unrelated healthy controls. The heterozygous mutation detected in this study has not yet been reported as pathogenic in literature or variant databases. We detected a heterozygous mutation in the BRPF1 gene for the first time in a consanguineous Saudi family. Furthermore, our finding explain and support previous finding along with possible additional features of IDDDFP that the mutation in BRPF1 gene play an important role to lead the Intellectual developmental disorder with dysmorphic facies and ptosis.